PENGARUH KETERAMPILAN GURU MENGGUNAKAN MEDIA PEMBELAJARAN TERHADAP PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM - Aidil Saputra (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2019)
Islamic education serves as an effort to educate Islamic religion and its values to be the way of life for students. Media is one of the important parts inIslamic learning practice used as means of delivering instruction in the teaching and learning activities to help students understand about Islamic religion. Satisfying learning achievement is a goal and desire for every educator and student. For students, the satisfying achievement is the result of the effort they have done during the teaching and learning activities. Whereas for educators, satisfying achievement is a measure of success in the learning activities. The impact of the use of instructional media usedby Islamic Education teachers on student achievement achieves good results. In conclusion, from the results of this study, it is proven that the media is very influential on student learning achievement, can improve independent behavior, easier to understand and get good experience in the learning process.